A hybrid-duplex system with joint detection for interference-limited UAV communications - Tan, Ernest Zheng Hui (2020)
In this paper, the advantages of joint detection (JD) in a hybrid-duplex unmanned aerial vehicle (UAV) communication system (HBD-UCS) are investigated as a step toward addressing spectrum scarcity in UAV communications. Through extensive outage probability and finite signal-to-noise-ratio diversity gain analysis, we showed that the performance of JD is independent of the strength and the data rate of the inter-UAV interference signal. On the contrary, the successive interference cancellation (SIC) detector requires the data rate of the interfering UAV to be less than the ground station before meaningful performance can be seen. At the system level, it is observed that the half-duplex UAV communication system outperforms the HBD-UCS with JD at moderate and high SNR regimes, as the latter is constrained by self-interference at the full-duplex ground station. Finally, we investigated the multiplexing gain region and showed that the joint detector offers higher diversity gain over a wide range of multiplexing gains over the interference ignorant and the SIC detector.